L'Oggetto, il Mobile, l'Interno. (Roma : Associazione Culturale Il Polittico, 1996)
Keen, Anna ; Ricci, Lithian ; Bertocci, Carlo ; Livadiotti, Massimo ; Abate, Alberto ; Fiorentino, Paolo ; Dulbecco, Gian Paolo ; Giletta, Franco ; Russo, Salvo ; Pulvirenti, Salvatore ; Bordone, Beatrice ; Kapor, Ana ; Fabrizi, Stefania ; Clink, Lucy ; Corey, Thomas ; Bartolini, Ubaldo ; Bada, Carlos Forns ; Marci, Tito ; Arcangeli, Giovanni
L'Oggetto, il Mobile, l'Interno, Associazione Culturale Il Polittico, Roma, 1996
boek